bHLH transcription factor family identification, phylogeny, and its response to abiotic stress in Chenopodium quinoa - Xue, Guoxing; Fan, Yue; Zheng, Chunyu; Yang, Hao; Feng, Liang; Chen, Xingyu; Yang, Yanqi; Yao, Xin; Weng, Wenfeng; Kong, Lingyan; Liu, Chuang; Cheng, Jianping; et al. (Frontiers in Plant Science, 2023)
The second-largest transcription factor superfamily in plants is that of the basic helix-loop-helix (bHLH) family, which plays an important complex physiological role in plant growth, tissue development, and environmental adaptation. Systematic research on the Chenopodium quinoa bHLH family will enable a better understanding of this species. A total of 218 CqbHLH transcription factor genes were identified in the whole genome, located on 18 chromosomes. A phylogenetic tree was constructed using the CqbHLH and AtbHLH proteins to determine their homology, and the members were divided into 20 subgroups and one unclustered gene. We also analyzed 218 CqbHLH genes, conservative motifs, chromosome diffusion, and gene replication. To study the evolutionary relationship and homology among multiple species, we constructed one Neighbor-Joining (NJ) tree and a collinearity analysis map of the bHLH family in C. quinoa and six other plant species. In addition, the expression levels of 20 CqbHLH members from different subgroups in various tissues, different fruit developmental stages, and six abiotic stresses were analyzed. We identified 218 CqbHLH genes and studied their biological functions, providing a basis for better understanding and further studying the bHLH family in quinoa.